Contact Dermatitis Associated with Preservatives: Retrospective Analysis of North American Contact Dermatitis Group Data 1994-2016 - Atwater, Amber Reck (J Am Acad Dermatol, 2021)
BACKGROUND: Preservatives are often necessary components of commercial products. Large scale North American studies on preservative allergy are limited. OBJECTIVE: To evaluate demographics, positive patch test reactions (PPTR), clinical relevance and trends for preservatives tested by the North American Contact Dermatitis Group (NACDG). METHODS: We conducted retrospective cross-sectional analysis of NACDG patch testing results of preservatives from 1994–2016. RESULTS: 50,799 patients were tested; 11,338 (22.3%) had a PPTR to ≥1 preservative. The most frequent reactions were to methylisothiazolinone (MI) 0.2% aqueous (aq) (12.2%), formaldehyde 2% aq (7.8%), formaldehyde 1% aq (7.8%), quaternium-15 2% petrolatum (pet) (7.7%) and methyldibromo glutaronitrile/phenoxyethanol (MDBGN/PE) 2% pet (5.1%). Paraben mix 12% pet (1%), iodopropynyl butylcarbamate (IPBC) 0.1% pet (0.4%), benzyl alcohol 1% pet (0.3%) and phenoxyethanol 1% pet (0.2%) had the lowest PPTRs. Linear regression analysis of preservatives tested revealed that only MCI/MI 0.01% aq (parameter estimate (PE) 0.42; CI 0.17–0.66; p<0.005) had a significant increase in PPTRs over time. LIMITATIONS: Collected variables are dependent on clinical judgment. Results may be prone to referral selection bias. CONCLUSION: This large North American study provides insight on preservative PPTRs and trends from 1994–2016.